Pelatihan Strategi Pemasaran Melalui Media Sosial Bagi UMKM untuk Memperluas Pasar di Desa Dolok Kahean - Ary Rizky Akbar; Ahmad Afandi (Lembaga Pengembangan Kinerja Dosen, 2025)
Rengginang Ibu Saliem Micro, Small, and Medium Enterprises (MSMEs) in Dolok Kahean Village still rely on conventional marketing systems (word of mouth), resulting in limited market reach and the absence of digital presence. This service aims to overcome this gap through training and mentoring of social media marketing strategies to increase brand awareness and expand market coverage. The method used is descriptive qualitative with a focus on participatory action and direct practice which is carried out through four stages, namely observation, interview, implementation, and evaluation. The results show the success of creating an official digital presence for MSMEs through the creation and management of Instagram and WhatsApp Business accounts. Assisted partners gain new operational skills and awareness that the use of social media is a strategic obligation to increase consumer awareness. Social media marketing strategies are proving to be effective as a low-cost solution to significantly expand market reach. This program has succeeded in creating a sustainable empowerment model and provides a foundation for MSMEs to continue digitization independently.